Syjoniści kontra „Żydzi polscy”. Palestyńskie echa memoriału Tuwima - Sobelman, Michał (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2014)
The article discusses the reception of Tuwim’s manifesto in Israel, focusing in particular on the 1940s. The author analyses various critical reponses to the poem expressed by Jewish critics in Palestine. Tuwim’s reception in Israel is presented from a new perspective which has not been explore so far.